Government mechanism in managing natural disasters in Malaysia: achievement factors - Azuddin Bahari; Zul Azhar, Zahid Jamal, Prof. Dr.; Kamarudin, Hussin, Brig. Jen. Dato' Prof. Dr. (Diponegoro University, 2008)
Organized by Diponegoro University, 10th - 11th September 2007 at Diponegoro University, Semarang, Indonesia.